1993
DOI: 10.1002/1097-0142(19930801)72:3<683::aid-cncr2820720310>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus antibody in patients with primary liver cancer (hepatocellular carcinoma, cholangiocarcinoma, and combined hepatocellular-cholangiocarcinoma) in Japan

Abstract: Background. In hepatocellular carcinoma (HCC), a high prevalence of hepatitis C virus antibody (anti‐HCV) has been reported, indicating that it may be an important etiologic factor in the pathogenesis of HCC. In this study, the authors investigated the prevalence of anti‐HCV in HCC patients, as well as the same prevalence in patients with cholangiocarcinoma (CC) and combined hepatocellular–cholangiocarcinoma (combined HCC‐CC), to study the clinicopathologic features of anti‐HCV–positive cases. Methods. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 20 publications
3
73
2
Order By: Relevance
“…A US cohort of individuals found HBV nucleic acids in ICC. Furthermore, recent studies show that HBV has been suggested to be involved in the pathogenesis of ICC through the inflammatory process (Tomimatsu et al, 1993;Reeves and DeMatteo, 2000;Liu et al, 2003). These strongly support the notion that HBV can be associated with ICC even in the absence of cirrhosis (Perumal et al, 2006) and further support the potential role of HBV infection in the pathogenesis of biliary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A US cohort of individuals found HBV nucleic acids in ICC. Furthermore, recent studies show that HBV has been suggested to be involved in the pathogenesis of ICC through the inflammatory process (Tomimatsu et al, 1993;Reeves and DeMatteo, 2000;Liu et al, 2003). These strongly support the notion that HBV can be associated with ICC even in the absence of cirrhosis (Perumal et al, 2006) and further support the potential role of HBV infection in the pathogenesis of biliary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Only three similar cases [19,22,30] have been previously reported, and this condition is considered to be very rare. According to several earlier reports [37][38][39] , hepatitis C virus (HCV)-related chronic hepatitis and cirrhosis are major risk factors for both HCC and CCC. The patient described in this report was found to be positive for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…While a¯atoxin B, a major etiological factor from speci®c region in China, is usually not considered as a risk factor in Hong Kong and Taiwan. On the contrary, chronic hepatitis C infection is more commonly observed in Japan, United States and Europe and recently, the association of chronic HCV infection and HCC has been reported from these regions (Tomimatsu et al, 1993;Gerber et al, 1992). Furthermore, HCC associated with chronic alcoholic liver disease and hemochromatosis are more commonly reported from Western populations such as Australia, Europe and United States.…”
Section: Discussionmentioning
confidence: 99%